THE EFFECT OF THE SYNBIOTIC ON REDUCING BODY WEIGHT, FEED CONSUMPTION, ACTIVITY AND HEALTH STATUS OF EXPERIMENTAL ANIMALS - W. F. J. Al-Fahdawy,; A. A. Alshaikh Daher, (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2023)
The current study aims to demonstrate the effectiveness of the synbiotic of eukaryotic and prokaryotic probiotics on the average weights of experimental animals (male rats) per week, the weights of the fed they consume, their activity and their health status daily by dosing each group with a probiotics and synbiotic except for the two control groups (positive and negative) were used. The results showed  a decrease in the weights of experimental animals that were dosed with probiotics L.GG, S.boul., L.GG+ S.boul. and the synbiotic (L.GG+ S.bou.l+Psy) even though they were fed a standard diet with adding 10%Kcal, the synbiotic group L.GG+S.boul. +Psy was the most efficient and capable in reducing the rats weight by 11.7% as compared to the positive control group (cont2). The synbiotic group was closest to the negative control group (cont1), at a rate of 4.06%, since the latter feeds on a regular standard diet only, and the decrease in the body weights of the experimental animals of the dosed groups is accompanied by a decrease in the amount feed of consumed for the group of rats that were dosed with synbiotic, reaching a decrease of 8.34% when compared with the cont2 group, while the percentage of feed consumption  was 0.73% when compared with the cont1 group. All dosed groups showed an inmprovment in activity and health status compared to the both control groups.